Sosialisasi Fiqih Shalat Jum’at Pra-Pelaksanaan Shalat Jum’at - Mappanyompa, Mappanyompa; Saprun, Saprun; Sahwan, Sahwan (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2024)
Among the obligatory prayers apart from the five daily prayers, namely the Friday prayer, which is fardhu'ain for every Muslim, male, sane and healthy. It is so important that Friday prayers are carried out in accordance with the explanation in Surah Al-Jum'ah, and the wisdom of Friday prayers is prescribed and one of its virtues is that Muslims gather together. The method used in this service is the lecture, question and answer method, where this service is carried out by providing understanding to the public about fiqh, namely conducting studies regarding Friday prayers, by bringing in speakers who have scientific discipline in the field of fiqh. The results of this community service are: First, increasing the knowledge of the congregation regarding how to perform Friday prayers in accordance with the guidance of the Prophet Muhammad. Two, this activity has an impact on increasing public understanding of the application of Islamic law in accordance with the guidance in the Sunnah Fiqh Book with a concentration on the Friday Prayers chapter. Third: Become a motivation for the congregation to start holding Friday prayers at the housingarea Griya Sehati.